Synthesis of bismuth oxide nanoparticles using bismuth nitrate and urea - Jha, Ratnesh Kumar; Pasricha, R.; Ravi, V. (Ceramics International, 2005)
A mixture of bismuth nitrate and urea is taken in 1:5 molar ratio and heated on hot water bath. A precipitate is formed on evaporation of the water which on decomposition at 400 degrees C produces nanocrystalline Bi2O3 particles. Formation of nano crystallites of Bi2O3 is confirmed by X-ray diffraction (XRD) study. Transmission electron microscopy (TEM) investigations revealed for these powders an average particle size of 50 nm. (c) 2004 Elsevier Ltd and Techna Group S.r.l. All rights reserved.
Keywords: calcination; Electron microscopy; X-ray methods